The Effects of a Program for Parents Responding to Children with Difficult Temperament on The Temperament of Preschool Children - Deepaen, Sweena; Siriumpunkul, Panida; Nirattharadorn, Mayuree (Journal of The Royal Thai Army Nurses, 2020)
The purpose of this quasi-experimental study was to examine the effects of a program for parents responding to children with difficult temperament. Parents meet the inclusion criteria were randomly assigned to the experimental and control groups with 40 participants in each group. The data were collected using the assessment for temperament form for Parents. Data were analyzed using descriptive statistics and t-test. The results indicated that the mean posttest score for the assessment for temperament in the experimental group after participating in the program was statistically significantly lower than the mean pretest score, and the mean posttest score in the experimental group after participating in the program was statistically significantly lower than the mean control group score (p <.001). The program for parents responding to children with difficult temperament helped parents in improving their self-regulation skill and enhancing ability to respond to their children with difficult temperament properly.